Early Follow-up for a Hybrid Total Hip Arthroplasty Using a Metal-Backed Acetabular Component Designed to Reduce “Backside” Polyethylene Wear - Poole, Colin E. (Springer-Verlag, 2005)
Modular acetabular systems have several advantages; however, increased polyethylene wear has been recognized as a disadvantage. In our study, an acetabular shell design with a highly polished inner surface, a locking mechanism that minimizes micromotion, and a high polyethylene liner to shell conformity was evaluated. A prospective cohort of 50 consecutive hips was followed up for a mean of 3.6 years (range, 2–7 years). One patient required an early revision for recurrent instability. Mean linear head penetration rates were 0.242 mm/year (range, 0.048–0.655 mm/year). The true linear wear rate was calculated after subtracting the linear wear in the first follow-up year from the total wear at the end of the follow-up. The true linear wear rate was 0.173 mm/year (range, 0.03–0.423 mm/year). A positive correlation was found between wear rate and male gender. The low head penetration rates suggest that a polished liner with an improved locking mechanism and increased liner conformity can reduce polyethylene wear.